2023
DOI: 10.3390/info14060329
|View full text |Cite
|
Sign up to set email alerts
|

Condition Monitoring and Fault Detection in Small Induction Motors Using Machine Learning Algorithms

Sayedabbas Sobhi,
MohammadHossein Reshadi,
Nick Zarft
et al.

Abstract: Electric induction motors are one of the most important and widely used classes of machines in modern industry. Large motors, which are commonly process-critical, will usually have built-in condition-monitoring systems to facilitate preventive maintenance and fault detection. Such capabilities are usually not cost-effective for small (under ten horsepower) motors, as they are inexpensive to replace. However, large industrial sites may use hundreds of these small motors, often to drive cooling fans or lubricati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Techniques based on machine learning models often use specific signals such as vibration, sound, current, and thermal images [21], [22], [23], [24], [25]. Alternatively, data can be converted to another format and then feature extracted, or neural networks can be used to perform fault diagnosis using temporal and spatial features Deep learning algorithms are also used for fault diagnosis of induction motors.…”
Section: Advances In Ai Driven Fault Detection Algorithmsmentioning
confidence: 99%
“…Techniques based on machine learning models often use specific signals such as vibration, sound, current, and thermal images [21], [22], [23], [24], [25]. Alternatively, data can be converted to another format and then feature extracted, or neural networks can be used to perform fault diagnosis using temporal and spatial features Deep learning algorithms are also used for fault diagnosis of induction motors.…”
Section: Advances In Ai Driven Fault Detection Algorithmsmentioning
confidence: 99%
“…The IMs are ensembles of important parts like the stator, the rotor, the windings, the rotor shaft, the fan, and the bearings of the shaft and the fan [4,11]. Additionally, several works have found that the previously mentioned components are associated with specific machine faults [12,13]; to this respect, the most common faults correspond to bearing damage in the range of 40% to 51%, followed by stator problems between 16% and 40%; the next are rotor damages with 5% to 10%, and other associated problems appear in a range of 12% to 28% [11,12,14]. Therefore, it is noticed that second major problems found in IMs are an electric type associated with the stator component, particularly, the stator winding faults (SWFs) such as short circuits and damage occurring turn-to-turn, coil-to-coil, phase-to-phase, or phase-to-ground [11].…”
Section: Introductionmentioning
confidence: 99%